Social media use among small and medium enterprises: a case of fashion industry growth - Gekombe, Caleb; Tumsifu, Elly; Jani, Dev (University of Dar es Salaam Library Journal, 2020)
This article examines how social identity, perceived usefulness and perceived ease of use influence the use of social media in SMEs and whether the use of social media influences the growth of fashion SMEs in Kenya. A survey involving 394 owner-managers of fashion SMEs from Nairobi and Kiambu counties was done, using a structured questionnaire; and multivariate analysis was done through structural equations modelling. Social identity and perceived ease of use bore significant influence on the usage of social media whereas perceived usefulness showed no significance in influencing owner-managers ' intention to use social media. The use of social media on the other hand had a significant influence on SME growth. Social media usage is considered useful in business but there is no motivation towards usage by the owner-mangers. Policy makers can therefore provide an enabling environment to encourage use of social media by SMEs. This study sought to find out whether or not the use of social media has a direct effect on growth of SMEs.